Mechanical response of dot-by-dot wire-and-arc additively manufactured 304L stainless steel bars under tensile loading. (7th February 2022) - Laghi, Vittoria; Palermo, Michele; Tonelli, Lavinia; Gasparini, Giada; Girelli, Valentina Alena; Ceschini, Lorella; Trombetti, Tomaso
Graphical abstract: Highlights: Mechanical response of Wire-and-Arc Additively Manufactured (WAAM) bars is affected by the geometrical irregularities. Tensile response is estimated through key effective mechanical parameters at the whole element's scale. Microstructural investigations highlight the same grain growth direction for bars printed at different build angles. The geometrical irregularities increase for increasing build angles. The key effective mechanical parameters present high scatter and reduced values for increasing build angles. Abstract: With the advent of a new arc-based additive manufacturing (AM) process, referred to as Wire-and-Arc Additive Manufacturing (WAAM), the scale of the metal printed parts increased up to several meters, thus becoming suitable for large-scale applications in marine, aerospace and construction sectors. However, specific considerations in terms of geometrical and mechanical properties ought to be made in order to effectively use the printed outcomes for structural engineering purposes. The introduction of the novel printing strategy referred to as "dot-by-dot", consisting in successive drops of molten metal, enabled the use of WAAM for complex lattice structures, made by continuous grids of WAAM bars. Nevertheless, their proper design requires an accurate evaluation of the influence of the non-negligible inherent geometrical irregularities on the mechanical response of the bars. Hence, extensive experimental work is needed in order to evaluate the mechanical response of WAAM bars with geometrical imperfections. The present study is thus focused on the assessment of the mechanical response in tension of WAAM-produced 304L stainless steel small bars in terms of key effective mechanical parameters. As such, the mechanical characterization through tensile tests is supported by microstructural investigations and detailed studies on the geometrical features. Three batches of bars are studied, each one printed at different build angles representative of limit cases for practical applications. The microstructural analysis confirms the preferential grain orientation typical of WAAM process for all three build angles. The results of the geometrical and mechanical characterization clearly evidence the non-negligible influence of the inherent geometrical imperfections on the mechanical response in tension of the printed bars, with a detrimental effect of the build angle on the main key effective mechanical parameters. Overall, the results highlight the need of specific investigations on both geometrical and mechanical properties of WAAM bars for structural design purposes.